2005
DOI: 10.1196/annals.1345.015
|View full text |Cite
|
Sign up to set email alerts
|

Objectives and Mechanism of Iron Chelation Therapy

Abstract: Prevention of cardiac mortality is the most important beneficial effect of iron chelation therapy. Unfortunately, compliance with the rigorous requirements of daily subcutaneous deferoxamine (DFO) infusions is still a serious limiting factor in treatment success. The development of orally effective iron chelators such as deferiprone and ICL670 is intended to improve compliance. Although total iron excretion with deferiprone is somewhat less than with DFO, deferiprone may have a better cardioprotective effect t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 38 publications
0
66
0
Order By: Relevance
“…This was in agreement with the gene expression data that showed a significant activation of inflammatory genes and with previously published results [41][42][43] and also with the human [45][46][47][48] . Iron degradation products accumulated near the implant surface and also in clusters of nearby cells, reminiscent of observations of non-physiological iron accumulation in lungs, where histiocytes have been shown to accumulate iron hydroxides as insoluble hemosiderin [49][50][51][52] . No iron ion overload reactions occurred in the vicinity of implants, suggesting that the observed inflammation was due to wound-healing responses and the accumulation of particulate matter in the tissue rather than to the biochemical effects of excess iron ions.…”
Section: Molecular Characterization Of the Implant-tissue Interactionmentioning
confidence: 99%
“…This was in agreement with the gene expression data that showed a significant activation of inflammatory genes and with previously published results [41][42][43] and also with the human [45][46][47][48] . Iron degradation products accumulated near the implant surface and also in clusters of nearby cells, reminiscent of observations of non-physiological iron accumulation in lungs, where histiocytes have been shown to accumulate iron hydroxides as insoluble hemosiderin [49][50][51][52] . No iron ion overload reactions occurred in the vicinity of implants, suggesting that the observed inflammation was due to wound-healing responses and the accumulation of particulate matter in the tissue rather than to the biochemical effects of excess iron ions.…”
Section: Molecular Characterization Of the Implant-tissue Interactionmentioning
confidence: 99%
“…2 Those chelators demonstrably reduce labile iron levels in plasma, but a few, by virtue of their membrane-crossing ability, also do so in cells. 1,10 However, whether such agents could or should be used in diseases in which regional iron accumulation is not accompanied by hyperferremia is questionable. In the present case, the goal of chelation is not merely systemic depletion, but redistribution of iron.…”
Section: Introductionmentioning
confidence: 99%
“…1 At the cellular level, labile iron begins to rise once the intracellular capacity for iron storage is surpassed, leading to catalytic formation of reactive oxygen species (ROS) that ultimately overwhelm the cellular antioxidant defense mechanisms and lead to cell damage. 2 In recent years, several pathologies have been shown to be associated with specific defects in cellular iron metabolism that do not give rise to conspicuous systemic iron overload.…”
Section: Introductionmentioning
confidence: 99%
“…(12) Biliary and blood excretion are the dual elimination mechanisms of deferoxamine, forming the final production in faeces and urine, respectively. (13) Generally, deferoxamine is injected subcutaneously for 8-12 hours per day at 40-60 mg/kg with the aid of an electronic pump. (14) A prospective study of 290 thalassaemia patients reported that a mean daily dose of deferoxamine at 51 mg/kg over one year resulted in a decrease of serum ferritin of 650 µg/L, which was more than what was observed when administering a dose of deferoxamine at 42 mg/kg.…”
Section: Discussionmentioning
confidence: 99%